Good temperature stability and fatigue-free behavior in Sm2O3-modified 0.948(K0.5Na0.5)NbO3–0.052LiSbO3 lead-free piezoelectric ceramics. (May 2015) - Hao, Jigong; Xu, Zhijun; Chu, Ruiqing; Li, Wei; Fu, Peng
Graphical abstract: Highlights: Sm2 O3 substitution shifts the polymorphic phase transition below room temperature. The temperature stability and fatigue behavior is improved by Sm substitution. The ceramics exhibit temperature independent properties and fatigue-free behavior. Abstract: The rare-earth oxide Sm2 O3 -doped 0.948(K0.5 Na0.5 )NbO3 –0.052LiSbO3 (abbreviated as KNN-LS5.2) lead-free piezoelectric ceramics were prepared using conventional solid sintering method. The effects of Sm2 O3 on the phase structure, electrical properties, temperature stability and fatigue behavior of KNN-LS5.2 ceramics were systematically studied. Results showed that Sm2 O3 substitution into KNN-LS5.2 induced a phase transition from coexistence of orthorhombic and tetragonal phase to a pseudocubic phase with a normal-relaxor ferroelectric transformation, and correspondingly shifted the polymorphic phase transition (PPT) below room temperature. Accordingly, the temperature stability and fatigue behavior of the modified ceramics were significantly improved. It was found that the KNN-LS5.2 ceramics with 0.6 mol% Sm2 O3 addition exhibited nearly temperature independent properties and fatigue-free behavior, together with its good electrical properties ( d 33 * = 167 pm/V, d 33 = 120 pC/N, k p = 33%, Q m = 101, ϵ r = 1326, tan δ = 4.6%). The results suggest that this material should be an attractive lead-free material for piezoelectric applications.